Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content 1. The Effect of a Proposed Educational Program Using Kinesthetic Storytelling on the Basic Motor Skills Grade One Students in Sultanate of Oman Mrs. Alya Masaud Hamdoon Al-Siyabi , Dr. Badria Khalfan Al-Hadabi 2. The effect of using multimedia in teaching Arabic Language on developing reading comprehension skills among Primary School Student in Al-Jizah district Mrs. Hala Nawaf Alzaben , Dr. Hamzeh Abdelfattah Alassaf 3. The Reality of Using the Blended Learning Strategy in Teaching Chemistry for Secondary School Students from the point of View of Teachers and Educational Supervisors in The Kingdom of Saudi Arabia Mrs. Wardah Gharman Alamri, Co-Prof. Ghadir Zinedine Felemban , Asst-Prof. Fadwa Felemban 4. The Impact of Using Problem-Solving Strategy on Metacognition Thinking and Motivation towards Learning Mathematics among Fourth Basic Grade Students in Jordan Mrs. Raidah Hassan Nimr Abdul Rahman, Prof. Odeh Abdel-Gawad Abu Sneineh 5. The effect of designing an interactive e-book on learning engagement for sixth graders with learning disabilities Mrs. Hessah Abdullah Al-Otaibi, Co-Prof. Abdel-Raouf Mohamed Ismail 6. Synthesis of Augmented Reality Use in the Development of English Language Writing Skills Mrs. Hadeel Hassan Al-Hazmi, Co-Prof. Mai M. Lutfi Al-Najami 7. The Effect of Using Interactive English Language E-Book for the Fourth Graders’ Listening and Reading Skills and Their Reflective Thinking at Martyr Yasseir Arafat Secondary School Mr. Mohammad Mahmoud Rjoob